Investigation of quality of cost data input in Life Cycle Cost (LCC) analysis in Malaysia - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (Kulliyyah of Architecture and Environmental Design, IIUM, 2016)

(untitled)
Commentators often pointed out the main focus of the local practitioners and scholars on LCC in the Malaysian construction industry is considerably on the LCC conversion which includes the methodology and models of computing LCC, but very little emphasis is given on the availability, accessibility, currency and reliability of the data as inputs into the process of generating reliable LCC analysis. This paper presents the application of modified Delphi as a fieldwork approach to investigate the current state and practice of LCC in the Malaysian construction industry with specific reference to data inputs of LCC. A three-round modified Delphi process was implemented to obtain consensus of expert opinion regarding the availability, accessibility, currency and reliability of data as inputs into the process of generating reliable LCC analysis. The results establish that the majority of modified Delphi panellists agreed there are several data sources that are categorized as very current and very reliable for LCC analysis. However, the majority of panellists reached consensus there is no single data source that is readily available and accessible for LCC analysis. The study verified the problem of getting quality data inputs for producing a comprehensive and reliable LCC analysis is crucial. It has been identified as one of the significant factors that impose constraints to the implementation of LCC practice for building works in the Malaysia construction industry.